Didacticism, Laughter, and New Spanish Cases in La portentosa Vida de la Muerte (1792), a Novel by Joaquín Bolaños - Molina Morales, Guillermo (2025)
In this article, we present a new interpretation of La portentosa Vida de la Muerte (1792), a text by the New Spanish author Joaquín Bolaños that has recently been brought back from obscurity. Our research is grounded in an aesthetic perspective that, drawing from Bakhtin and Beltrán, allows us to classify the work as a didactic novel, thus resolving certain critical misunderstandings. Within the framework of didacticism, laughter functions as a form of censure against undesirable human behaviors. In addition to the already extensively studied modern satire, we introduce the presence of Menippean satire, which connects the novel to the realm of traditions. Finally, we examine the depiction of the New World in the novel through three cases that stand out for their detailed portrayal within an essentially allegorical narrative framework.